Diaphragmatic ultrasound can help evaluate pulmonary dysfunction in patients with stroke - Chen, Yifei; Zhou, Shuyan; Liao, Lixia; He, Jinyan; Tang, Danzhe; Wu, Wen; Wang, Kangling (Frontiers in Neurology, 2023)
Objective: Pulmonary dysfunction after stroke has gradually received increasing attention from clinical and rehabilitation specialists. However, pulmonary function detection is challenging because of the cognitive and motor dysfunction of patients with stroke. This study aimed to detect a simple method for early evaluation of pulmonary dysfunction in patients with stroke. Methods: Forty-one patients with stroke in the recovery period (stroke group) and twenty-two matched healthy controls (control group) were included. We first collected baseline characteristics for all participants, with additional scale assessments on patients with stroke. Subsequently, we evaluated participants using the combination of simple pulmonary function detection and diaphragm ultrasound (B-mode) with ultrasound indexes, including the thickness of the diaphragm under the position of functional residual capacity (TdiFRC), thickness of the diaphragm under the position of forced vital capacity (TdiFVC), thickness fraction(TF), and diaphragmatic mobility（DM). Finally, we compared and analyzed all data to recognize group differences, correlations between pulmonary function and diaphragmatic ultrasound indexes, and correlations between pulmonary function indexes and assessment scales (National Institutes of Health Stroke Scale [NIHSS], Fugl–Meyer Assessment Scale [FMA], and Modified Barthel Index [MBI]) in patients with stroke, respectively. Results: The stroke group showed lower values in indexes of pulmonary and diaphragmatic function (P < 0.001), except for TdiFRC (P > 0.05). The majority of the patients with stroke had restrictive ventilation dysfunction, indicated by a significantly higher incidence ratio (36 in 41 patients) than those in the control group (0 in 22 patients) (P < 0.001). Significant correlations between pulmonary function and diaphragmatic ultrasound indexes were noted (P < 0.05), with the strongest correlation observed between TdiFVC and pulmonary indexes. In the stroke group, pulmonary function indexes were negatively correlated with the NIHSS scores (P < 0.001) and positively correlated with the FMA scores (P < 0.001). No (P > 0.05) or weak (P < 0.05) correlation with the MBI scores was found. Conclusions: Patients with stroke had pulmonary dysfunction even in the recovery period. Diaphragmatic ultrasound can be used as a simple and effective method for detecting pulmonary dysfunction in patients with stroke, with TdiFVC being the most effective index.